2018
DOI: 10.1136/bmjopen-2016-015604
|View full text |Cite
|
Sign up to set email alerts
|

Patient safety climate in general public hospitals in China: differences associated with department and job type based on a cross-sectional survey

Abstract: ObjectiveThis study analysed differences in the perceived patient safety climate among different working departments and job types in public general hospitals in China.DesignCross-sectional survey.SettingEighteen tertiary hospitals and 36 secondary hospitals from 10 areas in Shanghai, Hubei Province and Gansu Province, China.ParticipantsOverall, 4753 staff, including physicians, nurses, medical technicians and managers, were recruited from March to June 2015.Main outcome measureThe Patient Safety Climate in He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 49 publications
0
11
0
2
Order By: Relevance
“…Some studies have suggested that working environment deterioration of healthcare workers is associated with an increase in the number of event reports [11,12]; however, few studies have examined the influence of working hours, the number of night shifts, and the number of days off on patient safety culture. Working environment associated with each profession may affect patient safety culture differently because each profession has different working environment characteristics [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have suggested that working environment deterioration of healthcare workers is associated with an increase in the number of event reports [11,12]; however, few studies have examined the influence of working hours, the number of night shifts, and the number of days off on patient safety culture. Working environment associated with each profession may affect patient safety culture differently because each profession has different working environment characteristics [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Ten articles (13,14,17,18,20,22,24,25,27,33) used the HSOPSC questionnaire as data collection instrument; another ten articles (12,15,16,21,23,26,28,(30)(31)(32) used SAQ, and two (19,29) made use of PSCHO.…”
Section: Resultsmentioning
confidence: 99%
“…Demais fatores como comunicação ineficaz (Haytham et al, 2009), medo da culpabilização e vergonha frente ao erro (Zhou, Bundorf, Gu, He & Xue, 2015;Zhou et al, 2018) foram itens que apresentaram alto índice de respostas problemáticas.…”
Section: Discussionunclassified
“…Ginecologia e obstetrícia, pediatria, anestesiologia e departamentos auxiliares clínicos (E4).As amostragens foram de caráter multiprofissional e intersetorial, envolvendo funcionários desde a alta gestão até a assistência, reportados os últimos como funcionários da linha de frente. Apenas um estudo(Zhou et al, 2018) identificou todas as classes profissionais amostradas, os demais dividiram a análise em três categorias, sendo estas 1) gestores e chefes deSociety and Development, v. 10, n. 4, e28210414200, 2021 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i4.14200 em hospitais Veterans Affair (VA) nos Estados Unidos. A amostra de hospitais foi obtida mediante estratificação da amostra inicial em categorias…”
unclassified